Report of Working Group on Agricultural Chemicals (Fertilisers) Including Delivery System For Eighth Five Year Plan - Planning Commission (Planning Commission, 1989)
To identify the constraints and problems faced in the implementation of various programmes and suggest suitable measures legislative, administrative, institutional and others for overcoming the same with a view to accelerating the progress in the coming years.
Government of India Ministry of Agriculture and Cooperation
Government of India Ministry of Agriculture and Cooperation